Quality and carotenoid compositions of extrudates produced from composite biofortified maize (Zea mays L.) and soybean (Glycine max (L.) Merr.) flours - Adegunwa, M.O.; Ayanlowo, J.E.; Olatunde, G.O.; Adebanjo, L.A.; Alamu, Emmanuel Oladeji (Informa UK Limited, 2020)
Recently, the extrusion process has been applied to the production of snacks, cereals, and pasta due to the advantages it offers but processing temperature is a critical factor that affects the retention of nutrients in biofortified crops. This study examined the effect of extrusion cooking on the proximate, antinutritional, and carotenoid properties of biofortified maize and soybean flour blends. Samples were prepared by blending maize and soybeans flours in varied proportions (100:0, 90:10, 85:10, 80:20, 70:30) and were extruded at a feed rate of 1.5 kg/h with different temperatures and screw speeds. The extrudates were subjected to proximate, antinutritional, and carotenoid analyses using standard laboratory methods. The moisture content, crude protein, crude fibre, crude fat, and ash contents of the extrudates ranged from 8.89 to 12.91%, 8.21 to 20.61%, 2.08 to 4.64%, 3.81 to 5.90% and 1.62 to 2.37%, respectively. The comparative percentage composition of carotenoids of the flour blends indicated that lutein, zeaxanthin, β- cryptoxanthin, α-carotene, 13-cis β-carotene, 9-cis β-carotene, total β-carotene, total xanthophylls, provitamin A were higher when extruded at lower processing speed and temperature. The antinutrient composition shows a significant reduction in the levels of oxalate, tannins and phytate compared with previous related work. Sample ABM (90:10 biofortified Maize and soybean flours) showed high contents of carotenoid properties and low antinutritional properties and made it better than other samples. The extruded samples are nutritious, and further processing (addition of ingredients) will help derive a new product with increased nutritional quality.